Design of an Athermalizing Bonding Structure for Optical Components - Xiaofeng Liu; Xin Zhang; Xindong Chen (International Journal of Optics)
In this paper, an athermalizing connection method of the optical components of high-performance optical objectives that enables them to reduce the deterioration of their performance due to temperature instability is proposed. The optical components of the athermalizing connection structure consist of three parts arranged from the outside to the inside. The materials of the intermediate parts are different from those of the external and internal ones. The relationship between the parameters of the athermalizing connection structure is deduced based on the mechanics of materials. The surface errors of optical components at different temperatures are simulated for an exemplary structure. The simulation results show that the root mean square (RMS) of the optical component surface is approximately proportional to the temperature. When the temperature drops by 10 °C, the RMS changes by 0.66 nm as compared to its value measured at 20 °C. The temperature deflection test of the optical components carried out in the temperature range of 20 ± 5 °C provides the RMS values of the optical face of 0.019λ at 15 °C and 0.02λ at 25 °C. The change of RMS obtained in this test amounts to 0.63 nm for a temperature difference of 10 °C, which deviates from the respective simulated value by 4%. The experimental results show that the athermalizing connection method proposed in this paper ensures small deformations of optical components at large temperature changes. Therefore, it meets the requirements for the application of optical components and is suitable for the connection of high-precision components.